Improving Quality Education for Visually-Impaired Secondary School Students in Osun State with ICT-Based Tools - ODEKEYE, Ola Tokunbo; RAJI, Moromoke Nimota; ONOWUGBEDA, Franklin Ufoma; IGE, Michael Adeleke; ADEWUSI, Michael Adelani (Ilorin Journal of Education, 2024)
One of the goals of the SDGs is to ensure inclusive and equitable quality education which necessity equal learning opportunities for all students, regardless of their abilities, ethnic colour, race, sex, religion, language and disability. This study, therefore, investigated the availability and usability of ICT-based tools used in improving the quality of education of students with visual impairment in Osun State secondary schools. A descriptive survey method of research was employed. The sample size of the study was sixty (60) visually impaired students from two special secondary schools in Osun State. An instrument titled ICT-based Tools for Visually-Impaired Students (ICTVIS) was used for data collection. The reliability coefficient of the instrument obtained was 0.87 using the Split-half method. The findings revealed that some ICT-based tools were made available for visually-impaired students to improve the quality of their learning experiences. However, the study also demonstrated that visually-impaired students face some challenges in accessing and utilizing some of these available tools. It also revealed that there was no statistically significant difference in the challenges encountered by visually-impaired students when using ICT based on gender (t = 0.743, df = 58, p > 0.05). It was hereby recommended that the Ministry of Education should arrange various training skills programs, workshops, and conferences, for teachers teaching visually-impaired students how to teach with ICT-based tools and also government should provide more sustainable funding for ICT-based tools to ensure that students with visual-impairment also benefit the same quality of education as their peers without disabilities.